2022
DOI: 10.1002/alz.12850
|View full text |Cite
|
Sign up to set email alerts
|

A structural and resting‐state functional connectivity investigation of the pulvinar in elderly individuals and Alzheimer's disease patients

Abstract: In Alzheimer's disease (AD), structural and functional changes in the brain may give rise to disruption of specific cognitive functions. The aim of this study is to investigate the functional connectivity alterations in the pulvinar's subdivisions and total pulvinar voxel-based morphometry (VBM) changes in individuals with AD and healthy controls.A seed-based functional connectivity analysis was applied to the anterior, inferior, lateral, and medial pulvinar in each hemisphere. Furthermore, VBM analysis was ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 60 publications
0
7
0
Order By: Relevance
“…Furthermore, previous cognition studies of depressive patients have primarily focused on alterations in the hippocampus, amygdala, and cingulate gyrus, without considering functional alterations in other critical subcortical structures, such as the thalamus, and especially the pulvinar 14 . Such alterations may indicate a critical dynamic phase associated with subtle pathophysiological changes occurring before the manifestation of structural changes 15–17 . From that perspective, functional connectivity analysis is a valuable method for examining voxel‐wise functional magnetic resonance imaging (MRI) signals and that identifies functionally related brain areas and distributed networks.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, previous cognition studies of depressive patients have primarily focused on alterations in the hippocampus, amygdala, and cingulate gyrus, without considering functional alterations in other critical subcortical structures, such as the thalamus, and especially the pulvinar 14 . Such alterations may indicate a critical dynamic phase associated with subtle pathophysiological changes occurring before the manifestation of structural changes 15–17 . From that perspective, functional connectivity analysis is a valuable method for examining voxel‐wise functional magnetic resonance imaging (MRI) signals and that identifies functionally related brain areas and distributed networks.…”
Section: Introductionmentioning
confidence: 99%
“… 14 Such alterations may indicate a critical dynamic phase associated with subtle pathophysiological changes occurring before the manifestation of structural changes. 15 , 16 , 17 From that perspective, functional connectivity analysis is a valuable method for examining voxel‐wise functional magnetic resonance imaging (MRI) signals and that identifies functionally related brain areas and distributed networks. This therefore justifies an investigation of the differences between amnestic and other depressed individuals.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Here it is worth remembering that multiple studies conducted on neurodegenerative diseases have indicated that the presence of a compensatory hyperconnectivity network pattern is an early stage of dementia that precedes observable structural changes. 16,17,38 This suggests that the hyperconnectivity phase may serve as a compensatory response to the neurodegenerative process, occurring before the emergence of visible morphological evidence. Regrettably, this hyperconnectivity stage is ireversible, rendering any neuroprotective interventions implemented at a later stage potentially not sufficient.…”
Section: Vbm Resultsmentioning
confidence: 99%
“…Hence our finding of specific hippocampal functional changes without any structural evidence is unique in indicating a prestructural hippocampal compensatory phase in response to COVID. Here it is worth remembering that multiple studies conducted on neurodegenerative diseases have indicated that the presence of a compensatory hyperconnectivity network pattern is an early stage of dementia that precedes observable structural changes 16,17,38 . This suggests that the hyperconnectivity phase may serve as a compensatory response to the neurodegenerative process, occurring before the emergence of visible morphological evidence.…”
Section: Discussionmentioning
confidence: 97%